HUBUNGAN ANTARA VERTICAL JUMP, KEKUATAN OTOT PERUT, KELENTUKAN PERGELANGAN TANGAN DAN KECEPATAN SPRINT DENGAN KETEPATAN JUMP SERVICE (STUDI PADA ATLET BOLAVOLI PUTRA PORPROV KABUPATEN SUMENEP) - KURNIAWAN, HENDRA; Irsyada, Machfud (Jurnal Prestasi Olahraga, 2013)
One of Volleyball game techniques is the service motion. One element that is closely related to achievement was the procurement of the service motion. The success of an attack is determined by the accuracy in performing the service. Departing from the idea of the above authors tried to conduct research related to facilitate mastery of the techniques associated with the vertical jump, abdominal muscle strength, flexibility of wrist and speed sprint that can affect the accuracy of the jump serve. The researcher took the research title